Pengimplementasian Project Based Learning dalam Membangun Kompetensi Menulis Teks Berita Siswa dengan Muatan Kearifan Lokal - Novieanti, Linggar Iba; Sujinah, Sujinah; Fatin, Idhoofiyatul (Ideas Publishing, 2024)
In learning Indonesian in grade VII, students must have writing skills as one of the language skills. Project-based learning with local wisdom content not only improves students' writing skills, but also enriches their insight into the cultural values ​​around them. This study aims to improve students' news text writing competence through the application of project-based learning models. This study uses quantitative and qualitative research types and involves 33 students. The results showed that 63% of class VII-B students of SMP YP 17 Surabaya achieved KKM 75 with an average score for writing news texts of 72.45.